2022
DOI: 10.1126/sciadv.abn9874
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of the HIV-1 Pol polyprotein provides insights into virion maturation

Abstract: Key proteins of retroviruses and other RNA viruses are translated and subsequently processed from polyprotein precursors by the viral protease (PR). Processing of the HIV Gag-Pol polyprotein yields the HIV structural proteins and enzymes. Structures of the mature enzymes PR, reverse transcriptase (RT), and integrase (IN) aided understanding of catalysis and design of antiretrovirals, but knowledge of the Pol precursor architecture and function before PR cleavage is limited. We developed a system to produce sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“… 62 ). GagPol dimerization has been proposed to be driven by sequences in the RT and PR domains of GagPol ( 63 ) and GagPol dimers are less stable and less enzymatically active than mature PR dimers [( 64 , 65 ); see ref. 62 for review].…”
Section: Discussionmentioning
confidence: 99%
“… 62 ). GagPol dimerization has been proposed to be driven by sequences in the RT and PR domains of GagPol ( 63 ) and GagPol dimers are less stable and less enzymatically active than mature PR dimers [( 64 , 65 ); see ref. 62 for review].…”
Section: Discussionmentioning
confidence: 99%
“…The generation of the VBOF followed the methods described by Aller et al [17] Briefly, the process involved the following steps: (1) reference sequences of the HIV genome and proteins were obtained from the NCBI database, (2) the amino acids and dNTPs required to produce HIV units were estimated by multiplying each sequence by the reference copy number, [21][22][23] (3) the adenosine triphosphate (ATP) requirements of polymerizing amino acids were calculated by the metric that 4 ATPs and 1 PPi were needed for the formation of 1 peptide bond, and (4) the required amino acids, dNTPs, and ATPs were converted into mmol/g dray weight (DW) scale, and the reactions were created using Reaction function in COBRApy package.…”
Section: Vbof Constructionmentioning
confidence: 99%
“…However, it still could not resolve the structures of many proteins. For example, Harrison et al [13] published the protease (PR) and reverse transcriptase (RT) components of human immunodeficiency virus type-1 (HIV-1) Pol polyprotein using the cryo-EM method using in vitro expressed full-length Pol polyprotein. Integrase (IN) is largely not observed in the structures except for the first 49 amino acids 2 of 17 in the N-terminal domain (NTD) of IN identified via focused classification in the region expected.…”
Section: Introductionmentioning
confidence: 99%
“…Integrase (IN) is largely not observed in the structures except for the first 49 amino acids 2 of 17 in the N-terminal domain (NTD) of IN identified via focused classification in the region expected. The authors suggested that the cause is flexibility between RT and IN, and within the subdomains of IN [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation